VARIASI TERAPI GIGI DENGAN DIAGNOSA PULPITIS PADA PUSKESMAS DI KABUPATEN JEMBER TAHUN 2008 - Kiswaluyo, Kiswaluyo (IKESMA, 2010)
Dentists were in a difficult position in reaching that aim, because oftenly dentists with all of their limitation, compulsory gave ineffective treatment. This study wanted to know the differences of teraphies of pulpitis at Public Health Center Â in Jember. The methode done was descriptive based onÂ  Â the patient`s visit data from six PHC in Jember between March â August 2008 . The Result showed that there are many various teraphies on the pulpitis . This different treatment is influenced by some factors i.e facilities and patientâs need. Keywords : Pulpitis, treatment plan